ELECTRIC AND THERMOELEC PROPERTIES OF COMPOSITES WITH CARBON NANOTUBES LaNi5 - Нищенко, М.; Приходько, Г.; Шевченко, М.; Дубовий, А.; Михайлова, Г.; Ковальчук, Б.; Бозбей, Ю.; Азнакаєва, Д.; Московка, В. (Science-based technologies, 2011)
Electrical and thermoelectric properties of nanocomposite microparticles LaNi5 and carbon nanotubes (CNT) with an average diameter of 10 ± 2 nm were studied in the process of establishing electrical contact between the compression deformation, which leads to a change in the orientation and geometry of CNT. Electrical conductivity (σ) of composite with 19,7 weight % CNT is an order of magnitude higher in comparison with the σ array CNT, and with concentrations CNT less than 5 weight % Seebeck coefficient (which has a positive sign) is decreasing by order. Mechanism of growth σ and decline α is the transfer of conduction electrons from the metal to the CNT.